The berenstain bears go to camp - Berenstain, Jan (U.S.A : Berenstain inc, 1988)
The berenstain cubs enjoy day camp, although they are dubious about the end of season powwow and sleep-out at the top of skull rock.
Keywords: Camping -- fiction; Bear -- Fiction